LIGHT AND VISION - Mueller, Conrad G., author 648408; Rudolph, Mae author 648407; Time-Life Books 11642 (New York, NY : Time-Life Books Inc., 1980)
Vision and the light that make vision possible have been two of the most fascinating subjects throughout the history of science. Long before the Christian era, men knew enough about the anatomy of the human eye to perform cataract operations with crude instruments, and Hero of Alexandria had discovered one of the physical laws governing light. During certain periods in the year that followed there was little or no progress in the studies of light and vision. At other times, there were dramatic advances. There was, for example, a German biologist who learned a fundamental secret of the visual system by peering into the eye of a frog. And there was the British scientist, Sir Isaac Newton, who found the composition of light by taking it apart with one prism and restoring it with another. This book tells what science has learned through the ages about light and vision, describe the vital findings and charts the areas still to be explored. Each chapter has a supplementary picture essay that may be read independently. For example, Chapter 5, "Exploring the Spectrum," deals with the behavior of colors and is followed by a picture essay, "The Paradox of Color," that shows how man studies and uses the laws of color.